Unlocking the hidden variation from wild repository for accelerating genetic gain in legumes - Singh, Gurjeet; Gudi, Santosh; Amandeep,; Upadhyay, Priyanka; Shekhawat, Pooja Kanwar; Nayak, Gyanisha; Goyal, Lakshay; Kumar, Deepak; Kumar, Pradeep; Kamboj, Akashdeep; Thada, Antra; Shekhar, Shweta; et al. (Frontiers in Plant Science, 2022)
The fluctuating climates, rising human population, and deteriorating arable lands necessitate sustainable crops to fulfil global food requirements. In the countryside, legumes with intriguing but enigmatic nitrogen-fixing abilities and thriving in harsh climatic conditions promise future food security. However, breaking the yield plateau and achieving higher genetic gain are the unsolved problems of legume improvement. Present study gives emphasis on 15 important legume crops, i.e., chickpea, pigeonpea, soybean, groundnut, lentil, common bean, faba bean, cowpea, lupin, pea, green gram, back gram, horse gram, moth bean, rice bean, and some forage legumes. We have given an overview of the world and India's area, production, and productivity trends for all legume crops from 1961 to 2020. Our review article investigates the importance of gene pools and wild relatives in broadening the genetic base of legumes through pre-breeding and alien gene introgression. We have also discussed the importance of integrating genomics, phenomics, speed breeding, genetic engineering and genome editing tools in legume improvement programmes. Overall, legume breeding may undergo a paradigm shift once genomics and conventional breeding are integrated in the near future.